Thematic Learning – Integrative on Cross Curriculum in Social Studies and Language Learning in Elementary Schools on Higher Grade - Muzaki, Ferril Irham (Universitas Negeri Surabaya, 2018)
The purpose of this research is (1) to install the concept of thematic learning in Language teaching, (2) integration of learning concept of Language with subjects with Social Science subject and (3) integration between social science teaching materials and Indonesian language learning in elementary school. The research method used in this research is a classroom action research consisting of two cycles, the first cycle focuses on the understanding of thematic learning through interactive media, and in the second cycle focuses on understanding the improvement of understanding through the play approach. The result of this research is (1) there is an increase of understanding of thematic concept in flood prevention, (2) there is an increase of knowledge about the use and selection of diction for scientific activity at elementary level and (3) there is increasing comprehension of integrated concept between learning process and process scholarship that occurs in the classroom. Based on the above results it can be concluded that the thematic learning in elementary school in the Language teaching field even though developing the concept of learning across the curriculum. It is suggested to the beneficiaries to use the concept of language learning across the curriculum in learning Indonesian in elementary school. Keywords: Language Learning, Cross Curriculum, Thematic Review